After whom is herschel island named? - Burn, C. (Christopher R.) (ARCTIC, 2009)
Herschel Island (Qikiqtaruk) is a seasonally inhabited island off the western Arctic coast of Canada. It was designated as a Yukon territorial park under the Inuvialuit Final Agreement (1987) in recognition of its physical and cultural significance. The island was named by Captain John Franklin of the Royal Navy on 15 July 1826, during his second voyage of Arctic exploration. Unlike entries for other features named by Franklin along this coast, the journal record of this event does not indicate the specific person after whom he named the island. Franklin's journal and his published account state only that he wished to honour the name Herschel, borne most prominently by Sir William Herschel, who discovered the planet Uranus, Sir William's sister Caroline Herschel, who discovered eight comets, and Sir William's son Sir John Herschel, the brilliant polymath; in other words, he wished to honour this preeminent late Georgian scientific family.